Variación diurna de la materia orgánica particulada en una laguna costera del Golfo de California - Matínez López, A.; Gárate Lizáraga, I. (Revista de Biología Tropical, 1997)
Thee diel cyc1es of sampling were carried out in February, May, and October 1991 at the mouth of Bahía Concepción. This was done to describe t diurnal variability of size-fractionated phytoplankton abundance, species composition, pigments, and particulate organic matter (POM) in two depths. These variables show a very marked monthly variation, with February being the richest period in organic spices. Comparing the results obtained in t three cyc1es, we can observe that no significant differences (p=0.05 %) exist for both sampling levels during February and May. However, temperature, abundance, and species composition show significant diﬀerences (p=0.05%) betWeen sampling Levels during October. On the other hand, our results show a correlation between the import and export of organic matter policies during t tide phases. The analysis of variance shows significant diﬀernces (95 % confidence) in the POM concentrations in the February and October months. In February, the highest concentrations we recorded during the high tide. In October, an inverse condition was observed. The results of these cyc1es display the inﬂuenceof the Gulf of California waters ﬂowing into Bahía Concepción in February bringing in particulate organic matter. During October, a outﬂow of particles from the bay to the ocean was observed. In May á intermedian condition was observed